La méthode des éléments finis en lubrification: Une revue bibliographique - Bou-Saïd, Benyebka (European Journal of Computational Mechanics, 2001)
This paper deals with the review of the most important publications on the finite element modelling of lubricated mechanisms where flow particularities such as turbulence, overheating and fluid reactions due to its rheological properties appear. There are presented chronologically and discussed. Numerous mathematical developments and numerical simulations have performed until now. Nevertheless a lot of questions are still open such as cavitation and stress overshoot.